PERBANDINGAN PENDAPATAN PETANI PALA PADA BERBAGAI SALURAN PEMASARAN DI KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - Alvonda A. Kaunang; Caroline B.D. Pakasi; Jenny Baroleh; Joachim N.K. Dumais (Universitas Sam Ratulangi, 2014)
ABSTRACTAlvonda Agustiani Kaunang. Comparison of Farmers' Income On Various Marketing Channels in Kauditan Sub District North Minahasa regency. Under guidance of Dr. Caroline Pakasi BD, SP, MSi as chairman, Ir. Jenny Baroleh, MSi and Ir. Joachim N. K. Dumais, ME as members.The objective of this research is to determine the comparison of farmer’s income on varions marketing channel of nutmeg seed in Kauditan Sub District North Minahasa Regency. This research was conducted in Kauditan Sub District North Minahasa Regency from February 2014 to May 2014. Data collected in this study is primary data and secondary data. Primary data were obtained from 40 respondents nutmeg farmers, and secondary data obtained from institution associated with the research namely Department of Agriculture North Minahasa regency and office of Kauditan Sub District. Data were collected by system kuota.The results showed the greatest farmers Income is marketing channel 4, because the at marketing channel 4, as well as collecting large farmers. The farmer receives sales nutmeg from other farmers so that the amount of nutmeg production owned by the farmers to increase. At 4 marketing channels, farmers selling nutmeg inthe form of dried nutmeg because nutmeg dried selling price is greater than theselling price of crude nutmeg therefore the revenue received on marketing channel 4 was the greatest compared to the other marketing channel.